KINETIKA REAKSI TRANSESTERIFIKASI MINYAK KELAPA SAWIT - Jimmy, Jimmy (Jurnal Teknik Kimia, 2012)
Reaction kinetics data is one of the models which can help in making transesterification process efficient. This research aims to learn the kinetics of transesterification reaction of palm oil, and to make the research data usable as initial data for further research. To obtain the best kinetics data, we used temperature variation of 30, 45, and 60 oC, NaOH concentration of 1% of the oil weight, molar ratio of oil:methanol is 1:6. Reaction times used in this stud are2, 4, 6, 8, 10, 20, 30, 45, 60, 90 and 120 minutes. Transesterification of palm oil takes place in the second order reaction with temperature of 600C, the best reaction rate  0.0158 mol/(L.minute, reaction rate constant k1 = 1,6846x10-4 L/(mol.minute) and k2 = 5.1872x10-5L/(mol.minute), conversion 86.61% FAME(Fatty Acid Methyl Ester).